A STUDY ON THE INFLUENCE OF SOCIAL MEDIA ON YOGA PERCEPTION AND PRACTICE MOTIVATION IN MUMBAI’S WESTERN SUBURBS - *Dr. Sakshi Khatri, ** Prof Dilip Jain (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Originating over 5,000 years ago, Yoga remains a vital part of India’s cultural heritage and has gained global recognition for promoting inner peace and health. Social media is said to have played a key role in promoting yoga globally. The current study offers insights into how social media shaped perceptions of Yoga and motivated social media users to practice yoga. The study adopts a descriptive research design. Data were collected from 100 social media users from the Western Suburbs of Mumbai using a random sampling technique. Hypotheses were tested using the Chi-Square test. The result of the present study revealed that social media users' perceptions of yoga are influenced by the frequency of exposure to yoga content on social media, yoga influencers followed and the type of content shared by yoga influencers. Also, the duration of exposure to yoga content on social media per day and the frequency of engagement with yoga influencers motivate social media users to practice yoga.